The altered history of Willow Sparks - O'Connor, Tara (Oni Press, 2018)
Willow Sparks finds a magical book that allows her to literally change the circumstances in her life. But the more she changes, the greater the divide between her and her best friend Georgia, and the more dangerous the consequences.